2021
DOI: 10.1503/jpn.210006
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of TMS and neurophysiological biometrics in patients with schizophrenia

Abstract: Background: Transcranial magnetic stimulation can be combined with electromyography (TMS-EMG) and electroencephalography (TMS-EEG) to evaluate the excitatory and inhibitory functions of the cerebral cortex in a standardized manner. It has been postulated that schizophrenia is a disorder of functional neural connectivity underpinned by a relative imbalance of excitation and inhibition. The aim of this review was to provide a comprehensive overview of TMS-EMG and TMS-EEG research in schizophrenia, focused on exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 177 publications
(534 reference statements)
0
11
0
Order By: Relevance
“…In line with most studies, we noted no change in RMT in schizophrenia. 49 Similar to Tang et al ., 76 we found reduced MEP amplitudes in both schizophrenia groups. Furthermore, our MEP results are numerically similar to studies that found no difference from HC.…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations
“…In line with most studies, we noted no change in RMT in schizophrenia. 49 Similar to Tang et al ., 76 we found reduced MEP amplitudes in both schizophrenia groups. Furthermore, our MEP results are numerically similar to studies that found no difference from HC.…”
Section: Discussionmentioning
confidence: 53%
“…SICI resembles another indirect in vivo probe of GABA A -related activity. 45 , 49 Higher cortical inhibition seems to be associated with better motor execution and coordination. 50-53 A substantial body of evidence suggests reduced SICI in schizophrenia across different stages of this disorder.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Schizophrenia is a heterogeneous disorder varying in symptomatology, aberrant cortical connectivity, brain plasticity, complex comorbidities and medication uses which differentially affect TMS cognitive and neurophysiological effects 41 . To provide further insights into whether HF-rTMS targeting the LDLPFC or cerebellum vermis may be more promising for improving negative symptoms and cognition in schizophrenia, this study aimed to better understand the neurophysiological effects of rTMS to these two brain sites, by investigating effects on higher level neurocognitive function and electrophysiological measures, in healthy participants without confounding factors.…”
Section: Introductionmentioning
confidence: 99%